PS-020 The cost-effectiveness of screening for dihydropyrimidine dehydrogenase polymorphisms in cancer patients treated with fluoropyrimidines. (24th March 2015) - Cortejoso, L; García, MI; García, X; González-Haba, E; Sanjurjo, M; López-Fernández, L
Abstract : Background: Fluoropyrimidines are widely used in the treatment of several tumours such as colorectal and breast cancers. The toxicity caused by these drugs has been clearly associated with genomic variants in the dihydropyrimidine dehydrogenase (DPYD) gene. Purpose: To compare the cost of the screening for DPYD*2A and 2846 A >T mutations with the cost of treating fluoropyrimidine-induced severe neutropenia. Material and methods: The average cost of treating severe neutropenia (grade ≥ 3) in 10 cancer patients treated with 5-FU or capecitabine was calculated. Medical records were reviewed to calculate the health care resources used as the result of the adverse event (blood tests, secondary treatment and hospitalisation). A literature review was conducted to estimate the frequency of DPYD*2A or 2846A >T genetic variants and the proportion of patients with these variants developing adverse reactions grade 3–4. Results: The frequency of DPYD*2A in Caucasians was 0.9%, while DPYD 2846A >T occurs in 1.5%. A literature review showed that 682% of DPYD*2A and 74.3% of DPYD 2846A >T carriers would develop an adverse event grade ≥ 3 during treatment with fluoropyrimidines (approximately 17 out of 1, 000 patients). The average cost of genotyping 1, 000 patients for these two polymorphisms in our centre would be €10, 000 and the cost of treating an episode of severe fluoropyrimidine-induced neutropenia in 17 patients was €32, 300. As a result, €22, 300 would be saved for 1, 000 patients treated. Conclusion: Avoiding the costs of treating severe adverse reactions due to fluoropyrimidines may justify the costs of DPYD testing. Treatment with fluoropyrimidines guided by DPYD genetic testing could offer a more efficient health outcome versus empirical treatment. Further studies should be carried out to verify our findings. References and/or acknowledgements: No conflict of interest.